2017
DOI: 10.1007/s10973-017-6295-3
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical properties of chitosan nanocomposites with cellulose modified in ionic liquids

Abstract: In this paper, ionic liquid treatment was applied to produce nanometric cellulose particles of two polymorphic forms. A complex characterization of nanofillers including wide-angle X-ray scattering, Fourier transform infrared spectroscopy, and particle size determination was performed. The evaluated ionic liquid treatment was effective in terms of nanocrystalline cellulose production, leaving chemical and supermolecular structure of the materials intact. However, nanocrystalline cellulose II was found to be mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(28 citation statements)
references
References 65 publications
1
27
0
Order By: Relevance
“…MPa [33]. The TS values of films were comparable to those of plastic-based films, such as films based on LDPE (8-10 MPa), HDPE (19-31 MPa), EVOH (6-19 MPa), PCL (4 MPa), PS (31-49 MPa), PLA (45 MPa), PVC (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55), and PP (27-98 MPa) [50]. Li et al [69] found that the TS of the composite films increased from 85 to 120 MPa, with an increase of CNC content from 0 to 15 wt.%.…”
Section: Mechanical Propertiesmentioning
confidence: 68%
See 1 more Smart Citation
“…MPa [33]. The TS values of films were comparable to those of plastic-based films, such as films based on LDPE (8-10 MPa), HDPE (19-31 MPa), EVOH (6-19 MPa), PCL (4 MPa), PS (31-49 MPa), PLA (45 MPa), PVC (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55), and PP (27-98 MPa) [50]. Li et al [69] found that the TS of the composite films increased from 85 to 120 MPa, with an increase of CNC content from 0 to 15 wt.%.…”
Section: Mechanical Propertiesmentioning
confidence: 68%
“…T maxI (first stage) occurred at the range of 40-100 • C, which corresponds to a weight loss of ca. 14% and is attributed to the evaporation of residual acetic acid [52] and physical trapping of water and/or weakly hydrogen-bonded to CS molecules. The second stage (T maxII ) of weight loss at below 200 • C could be assigned to the initial degradation of the polymer and/or release of atypical, strongly hydrogen-bonded water.…”
Section: Equilibrium Moisture Content (Emc)mentioning
confidence: 99%
“…This includes saccharide ring dehydration, depolymerization, and decomposition of deacetylated and acetylated chitosan units. 54 , 55 …”
Section: Resultsmentioning
confidence: 99%
“…ChNPs can be synthesized using either “bottom-up” or “top-down” approaches and/or combination of both procedures. Moreover, Ch-derivatives and ChNP composites are prepared to enhance the performance of the pristine Ch, such as reducing agglomeration and improving overall stability [28]. For instance, a supplement of DNA and RNA into mammalian cells by gene delivery can be used for treating diseases either to express new proteins or to prevent the expression of existing proteins [29].…”
Section: Introductionmentioning
confidence: 99%